Análise de Cultivares de Sorgo para extração de etanol e produção de silagem - Zeferino, Gabriela Lionço (2015)
Four sorghum cultivars were evaluated for silage production and ethanol, two hybrid saccharine Sugargraze and ADV 2010 a varietal feed the Formoso and the BRS 506 varietal saccharine. To analyze the chemical characteristics was used completely randomized design. To compare the means used the Shapiro-Wilk test (P <0.05). In this context, the objectives of this study were to evaluate biomass production, evaluate the solid fractions and net production of ethanol and sugar, silage and mulch the entire plant. From the chemical analysis of cultivars, one can get the results of dry matter, organic matter, total carbohydrates, crude protein, ether extract, neutral detergent fiber, acid detergent fiber and hemicellulose. For hybrid sorghum Sugargraze, both the production of biomass, solid fractions and net production of ethanol and sugar, whole plant silage and bagasse stood out among the other cultivars. The chemical composition of sorghum cultivars, evaluating the whole plant and bagasse for silage, indicates that there is no difference, can use as both a one for silage.